Donor Warm Ischemia Time in DCD Liver Transplantation—Working Group Report From the ILTS DCD, Liver Preservation, and Machine Perfusion Consensus Conference. Issue 6 (June 2021) - Kalisvaart, Marit; Croome, Kristopher P.; Hernandez-Alejandro, Roberto; Pirenne, Jacques; Cortés-Cerisuelo, Miriam; Miñambres, Eduardo; Abt, Peter L.
Abstract : Donation after circulatory death (DCD) grafts are commonly used in liver transplantation. Attributable to the additional ischemic event during the donor warm ischemia time (DWIT), DCD grafts carry an increased risk for severe ischemia/reperfusion injury and postoperative complications, such as ischemic cholangiopathy. The actual ischemia during DWIT depends on the course of vital parameters after withdrawal of life support and varies widely between donors. The ischemic period (functional DWIT) starts when either SpO2 or blood pressure drop below a certain point and lasts until the start of cold perfusion during organ retrieval. Over the years, multiple definitions and thresholds of functional DWIT duration have been used. The International Liver Transplantation Society organized a Consensus Conference on DCD, Liver Preservation, and Machine Perfusion on January 31, 2020 in Venice, Italy. The aim of this conference was to reach consensus about various aspects of DCD liver transplantation in context of currently available evidence. Here we present the recommendations with regards to the definitions used for DWIT and functional DWIT, the importance of vital parameters after withdrawal of life support, and acceptable thresholds of duration of functional DWIT to proceed with liver transplantation.